PENGEMBANGAN ANALISIS BUTIR SOAL URAIAN BERBASIS ICT - Ilmi Fadhilah Marwa; Muhammad Kris Yuan Hidayatullah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to develop an application for analysis of item descriptions in desktop form to determine the feasibility of the Anabus Application based on the assessments of expert lecturers, expert teachers and teacher responses. This research is development research or (R&D) Research and Development which is adapted from the ADDIE development model. The development stage of the ADDIE model has 5 stages, including: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Validation was carried out by expert lecturers, expert teachers, and tested on 30 respondents, namely 30 educators at Al-Hikmah Sumobito Middle School, Jombang. The results of this research show that the level of feasibility of the Anabus application is: 1) The first media expert obtained a total score of 56.00, which is included in the "Very Good" category when presented, getting a score of 93,3%, where the percentage is included in the "Very Appropriate" category, 2) Media experts The second obtained a total score of 58.00, including the "Very Good" category. If presented, it received a score of 96.7%, where the percentage was included in the "Very Decent" category, 3) The third media expert obtained a total score of 50.00, including the "Very Good" category. If presented, it gets a score of 83,3%, where the percentage results are included in the "Very Decent" category. Educators' response to the Anabus application during the trial was 81.7%. Thus, you can see that the application for analyzing item descriptions (Anabus) is suitable for use as an application for analyzing item analysis in educational institutions.